Processing the ECG Signal by Means of the Digital Hartley Transform - Ursulean, R. (Elektronika ir Elektrotechnika, 2000)
The main advantages of the digital Hartley transform were used to show a new way to save memory and computing time when processing the ECG signal. The frequency domain samples for the digital Hartley transform of most common windows were computed and presented in a closed form. Their further use may significantly increase the computing speed.